Global Prevalence and Distribution of Human Sarcocystosis: A Systematic Review and Meta-Analysis - Jurairat Jongthawin; Aongart Mahittikorn; Kinley Wangdi; Frederick Ramirez Masangkay; Manas Kotepui (Tropical Medicine and Infectious Disease, 2026)
Human sarcocystosis is a neglected zoonotic infection caused by protozoa of the genus Sarcocystis. Although sporadic cases and outbreaks have been reported worldwide, the global burden of human infections has not been comprehensively synthesized. This study aimed to estimate the pooled prevalence and global distribution of Sarcocystis infections in humans. A systematic review and meta-analysis were conducted in accordance with PRISMA guidelines and registered with PROSPERO (CRD420251159944). PubMed, Scopus, Web of Science, Ovid, Nursing & Allied Health Premium, and Google Scholar were used for retrieving relevant studies. Observational studies published from 2000 onward reporting human Sarcocystis infections confirmed by microscopic and/or molecular methods were included. A random-effects model was used to estimate pooled prevalence. Heterogeneity was assessed using the I2 statistic. Subgroup analyses and meta-regression were performed to explore sources of heterogeneity. Seventeen studies comprising 66,329 participants met the inclusion criteria. The pooled prevalence of human Sarcocystis infection was 0.85% (95% confidence interval [CI]: 0.33–2.19), with substantial heterogeneity (I2 = 98.2%). Prevalence estimates showed marked variation across continents, countries, participant groups, diagnostic methods, Sarcocystis species, and clinical forms of sarcocystosis. Although human Sarcocystis infection appears relatively rare, its prevalence is geographically heterogeneous across studies published between 2000 and 2024. The robustness of the pooled prevalence estimate is limited by the small number of studies, uneven geographical coverage, and substantial heterogeneity. Differences in diagnostic approaches, study populations, infecting species, and disease phenotypes likely contributed to this variability. Enhanced surveillance and standardized application of sensitive molecular diagnostics are essential to better define the epidemiology, burden, and public health significance of human sarcocystosis.